ANALYSIS OF RECEIVABLES MANAGEMENT EFFECTIVENESS AND THEIR EFFECT ON COMPANY LIQUIDITY AT PT JACO NUSANTARA MANDIRI MEDAN - Hasibuan, Elwardi (Jurnal Ekonomi, 2022)
This study aims to determine the practice of receivable management and its effect on the level of liquidity of the company PT Jaco Nusantara Mandiri Medan. The sample in this study was taken from the financial statements of PT. Jaco Nusantara Mandiri Medan for three years, namely 2016, 2017 and 2018. The analytical method used is quantitative analysis using ratio analysis as a measuring tool. The results of the analysis carried out show that the company's receivables management has established a loose credit policy and a passive collection policy, as well as. Receivable Turn Over (RTO), ACP, and AIOR performance continues to decline every year. This decrease shows that the ineffective management of the company's receivables management will affect the decrease in the company's liquidity.